SENTIMENT ANALYSIS ON TWEETS ABOUT THE ELECTIONCANDIDATES ISING TEXTBLOB - Tlepova, Moldir (Journal of Emerging Technologies and Computing, 2024)
Sentiment analysis is the categorization of the speaker’s, writer’s, or other subject’s perspective on a certain issue. Since Kazakhstan’s presidential election in 2022 is one of the most discussed events we distinguish people’s perspectives on the election and each candidate. The possible leader of the country will be influenced by the public’s perception of a candidate. A diverse data set illustrating the current public perceptions of the candidates are gathered from the Twitter platform. The collected tweets are examined using a lexicon- based methodology TextBlob to ascertain the public’s sentiments. In this study, we analyze the collected tweets to identify the polarity andsubjectivity measures that provide light on the user perception of a certaincandidate.